Fiqh Al-Ikhtilaf and Science: A Discourse of Preliminary Differences of Lunation In Indonesia - Jayusman Jayusman; Oki Dermawan (Karsa: Journal of Social and Islamic Culture, 2018)
Differences of determination lunation initial always happened in Indonesia. Indonesia actually has a lot of experts in the field of falak and Astronomy, but make inductive inferences are often done. In this paper will discuss: What lies behind the differences early lunar month in Indonesia? How Fiqh al-Ikhtilaf and Science analyze the differences in the lunation beginning? How alternative unification lunation difference in the initial determination in Indonesia? The research method used is qualitative. This study uses the approach of Fiqh al-Ikhtilaf, astronomy, and falak. The collecting data techniques are documentation and interviews. Data analysis due to collect data process. Initial determination of the lunation differences in Indonesia's background are: difference understanding in syar'i argument, certain belief, methodological issues into theological and dogmatic. The problems analysis of differences in initial of lunation in Indonesia are associated with the method and results of calculations in preliminary determination, it is an area of science, related to the selection criteria for the initial month of the lunar is a Fiqh al-Ikhtilaf field. Bids for the initial determination of the difference unification lunation in Indonesia are: agreement methods and criteria are used as guidelines in determining the beginning of lunation, as well as the existence of an authoritative department that sets the initial lunation.